Administrative Reform in Jordan: Urgency for Reforming the Bureaucracy Structure - Tbaishat, Rami Mohd (International Review of Management and Marketing, 2015)
This study aimed to provide a diagnostic-analytic study of the characteristics of administrative reform experience in Jordan with a view to identify the pitfalls and shortcomings that accompanied it, based on assumptions in conducting reform. During the last twenty years, Jordan has witnessed a considerable effort in administrative reform. The result of such reform programs have fallen short of expectations and were rather limited in impact. Therefore, the analysis focused on the conditioned, under which the governing structure works efficiently, and how Jordan can direct its resources toward the achievement of efficiency in the public service with special emphasis on the bureaucracy structure. The study revealed that the private sector itself is unable to participate significantly in absorbing the labor force into the economy as a result of the monopoly problems existing in the public sector. Moreover, the lower share of spending on the capital category is vital in classifying the merits of government economic policies. Therefore adaptability is key to any reform and reorganization plan in which contingencies must be embedded in the process of organizational change and administrative action. Keywords: Jordanian bureaucracy; good governance; administrative reform; state. JEL Classifications: D71; D73; D78, H11